Quorum sensing inhibitory potential and in silico molecular docking of flavonoids and novel terpenoids from Senegalia nigrescens. (24th April 2018) - Bodede, Olusola; Shaik, Shakira; Chenia, Hafizah; Singh, Parvesh; Moodley, Roshila
Abstract: Ethnopharmacological relevance: Senegalia nigrescens is used in traditional medicine for the treatment of dysentery and convulsions. Aims of the study: This study was aimed at identifying bioactive compounds from S. nigrescens and carrying out in vitro and in silico anti-quorum sensing studies on the compounds. Materials and methods: Extracts of S. nigrescens were chromatographed repeatedly. The isolated compounds were characterised using NMR spectroscopy and mass spectrometry. The anti-quorum sensing potential of S. nigrescens crude extracts and selected phytochemicals was quantified using Chromobacterium violaceum quorum sensing-controlled violacein inhibition assays. Qualitative modulation of quorum sensing activity and signal synthesis was investigated using agar diffusion double ring assays and C. violaceum . Molecular docking was conducted to explore the binding conformations of ent -kaurene diterpenes and flavonoids into the binding sites of quorum sensing regulator proteins, CviR and CviR′. Results: Phytochemical investigation of S. nigrescens resulted in the isolation of a new ent -kaurene diterpenoid ( ent -kaur-15-en-18, 20-diol) alongside ent -kaur-15-en-18-ol, being isolated for the first time from a plant species. Other compounds isolated included 30-hydroxylup-20(29)-en-3 β -ol, 3 β -hydroxy-20(29)-en-lupan-30-al, lupeol, stigmasterol, a long chain alcohol (tetracosan-1-ol) and three flavonoids (melanoxetin, quercetin and quercetin-3- O -methyl ether). Structures of isolated compounds were elucidated using different spectroscopic techniques including 1D and 2D NMR. Inhibition of violacein production was concentration-dependent, with 56.52% inhibition being obtained with 200 µg of quercetin-3- O -methyl ether, while 53.38% inhibition was obtained with 600 µg of quercetin. Agar diffusion double ring assays indicated CviI synthase/CviR receptor modulation by S. nigrescens phytochemicals, suggesting that quorum signal synthesis was down-regulated and/or targeting binding of signal to the receptor. The computed binding energy data suggested that the flavonoids had a stronger tendency to inhibit both CviR and CviR′ with varying binding affinities. Conclusion: S. nigrescens crude extracts together with the novel ent -kaurenoids and flavonoids demonstrated potential anti-quorum sensing activity. S. nigrescens may thus represent a source of anti-quorum sensing therapeutic candidates for the control of existing and emerging infectious diseases. Graphical abstract: